تصور برنامج موسيقى مقترح لتنمية الانتماء للوطن داخل المدارس الدولية لطفل الروضة للحفاظ على هويته - إلياس، رانيا سمير Ilyas, Rania Samir (جامعة حلوان - كلية التربية الموسيقية, 2017)
يسعى الكثيرون إلى التعليم الدولي لما يميزه من خدمة تعليمية متميزة، وإعداد طالب متميز ذو سمات شخصية إيجابية، ولكن على الجانب الآخر لا نستطيع أن نغفل عن الأثر السلبي في غرس قيم وهوية وثقافة وسلوكيات الطلبة في المدارس الدولية، مما أدى إلى إفراز سلوكيات غير مرغوب فيها وعدم شعورهم بالانتماء للوطن وفقد هويته الثقافية. مشكلة البحث: من خلال تدريس الباحثة الأغاني الموسيقية للطالبة المعلمة ببرنامج اللغة الإنجليزية – بكلية التربية للطفولة المبكرة – جامعة القاهرة، وجدت الباحثة أنه هناك قصور في الأغاني المقدمة لطفل الروضة في المدارس الدولية التي تنمي الانتماء والثقافة المصرية من قيم ومعتقدات اجتماعية وانتماء للوطن والحفاظ على الهوية وغيرها لدى الطفل، مما دعي الباحثة للتفكير في إجراء هذا البحث وعمل برنامج موسيقي مقترح يقدم أغاني مصرية تنمي الانتماء والثقافة المصرية والهوية في المدارس الدولية. أهداف البحث: يهدف هذا البحث إلى إعداد برنامج موسيقي مقترح يساعد على الانتماء والحفاظ على الهوية المصرية لطفل الروضة في المدارس الدولية، وتكمن أهمية هذا البحث في دور الأغاني المصرية لغرس الانتماء والقيم والمعتقدات المصرية للحفاظ على هوية الطفل المصري وحبه وانتمائه لوطنه مصر. أهمية البحث: تكمن أهمية هذا البحث في دور الأغاني المصرية لغرس الانتماء والقيم والمعتقدات المصرية للحفاظ على هوية الطفل المصري وحبه وانتمائه لوطنه مصر. فرض البحث: تفترض الباحثة أن: -البرنامج الموسيقي المقترح قد يساعد على الانتماء والحفاظ على الهوية المصرية لطفل الروضة. -توجد فروق ذات دلالة إحصائية بين متوسطات درجات أطفال المدارس الدولية في الانتماء والحفاظ على الهوية المصرية عن طريق استخدام الأغاني الموسيقية المصرية أثناء التدريب في الاختبار البعدي لصالح المجموعة التجريبية. منهج وعينة البحث: يتبع هذا البحث المنهج التجريبي "المجموعة واحدة"، وتتكون عينة البحث من مجموعة من الأطفال بالمرحلة الثانية من الروضة بمدرسة Sunrise الدولية بمصر الجديدة وعددهم (15) طفل. أدوات البحث: -استمارة استطلاع رأي السادة الأساتذة المحكمين في الاختبار القبلي – بعدي لقياس مستوى الانتماء لطفل الروضة في المدارس الدولية. (إعداد الباحثة). -استمارة استطلاع رأي في الأغاني الموسيقية المقترحة لأطفال الروضة بالمدارس الدولية. -مقابلات فردية مع مجموعة من أطفال الروضة بمدرسة Sunrise الدولية بمصر الجديدة في نوع الأغاني ودورها في تنمية الانتماء. -مجموعة من الأغاني الموسيقية المصرية التي تحتوي على بعض المفاهيم التي تنمي الانتماء لطفل المدارس الدولية. وينقسم البحث إلى جزئين: أولا: الإطار النظري ويشمل: 1-دراسات سابقة عربية وأجنبية مرتبطة بموضوع البحث. 2-الانتماء والهوية ويشمل: مفهوم الانتماء – مظاهر الانتماء – البدائل الانتمائية للانتماء القومي – مستوى الانتماء – تعريف الهوية – بعض الحقائق عن طبيعة وأبعاد الهوية. 3-المدارس الدولية ويشمل: مصطلح المدارس الدولية – سمات المدارس الدولية – الإشكالية التربوية والثقافية من وجود نظام تعليم مختلف عن البيئة الأصلية – الآثار السلبية من انتشار ثقافة المدارس الدولية. 4-الموسيقى وطفل الروضة ويشمل: أهداف تدريس الموسيقى للطفل – أغنية الطفل – الأهداف التربوية لأغنية الطفل. ثانيا: الإطار التطبيقي ويشمل: -إجراءات التجربة. -جلسات البرنامج المقترح: وعددهم 5 جلسات. -نتائج البحث وتفسيرها: يتضح من عرض نتائج البحث أن البرنامج الموسيقي المقترح من قبل الباحثة يزيد من فاعلية الانتماء لدى طفل الروضة للمدارس الدولية في ضوء الإجابة على فروض البحث فقد أظهرت نتائج الفرض الأول وجود فروق ذات دلالة إحصائية لصالح درجات الأطفال في الاختبار البعدي، وتحقق درجة مرتفعة لدى الأطفال من الانتماء والحفاظ على الهوية المصرية لطفل الروضة في المدارس الدولية، مما يدل على أن البرنامج الموسيقي المقترح ساعد على الانتماء والحفاظ على الهوية المصرية لطفل الروضة. وأظهرت نتائج الفرض الثاني وجود فروق معنوية ذات دلالة إحصائية بين الدرجات الكلية للاختبار القبلي والاختبار البعدي، وكانت الإجابات لصالح الدرجات الكلية للاختبار البعدي، وقد بلغ حجم التأثير للتجربة 93.4% مما يشير إلى نجاح التجربة بشكل كبير على مستوى الدرجة الكلية للأطفال. وبناء على النتائج السابقة يتضح أن البرنامج الموسيقي المقترح من قبل الباحثة يزيد من فاعلية الانتماء لدى طفل الروضة للمدارس الدولية. -توصيات البحث: *توصي الباحثة بضرورة تدريس البرنامج الذي اقترحته الباحثة في الدراسة الحالية لتنمية الانتماء لأطفال المدارس الدولية. *ضرورة الاهتمام باستخدام جميع الأنشطة الموسيقية المقدمة لطفل الروضة في المدارس الدولية لتنمية الانتماء والحفاظ على هويته المصرية. *الاهتمام بتدريس الأغاني المصرية بالمدارس الدولية للحفاظ على الهوية المصرية لطفل الروضة. -المراجع.
Many individuals seek international education for its distinctive educational service and preparing excellent student having positive personality traits. On the other hand, we cannot neglect the negative impact of instilling values, identity, culture and behavior of international schools students, this led to undesirable behaviors and lack of sense of belonging to the homeland and its cultural identity. Research Problem: Through the researcher teaching musical songs for the student teacher in the English department - Faculty of Early Childhood - Cairo University, the researcher found a lack of songs provided for kindergarten child of international schools that develop Egyptian belonging and culture of values, social beliefs, homeland belonging and maintaining he identity of the child. The previous prompted the researcher to think of conducting this research and preparing a proposed musical program that provides Egyptian songs that develop the Egyptian belonging and culture and identity within international schools. Research Objectives: This research aims to prepare proposed musical program that helps in maintaining Egyptian belonging and identity of the kindergarten children in international schools. The importance of this research is represented in the role of Egyptian songs in instilling Egyptian belonging, values and beliefs in order to maintain the identity of the Egyptian child, his love and belonging to homeland Egypt. Research Importance: The importance of this research is represented in the role of Egyptian songs in instilling Egyptian belonging, values and beliefs in order to maintain the identity of the Egyptian child, his love and belonging to homeland Egypt. Research Hypotheses: researcher assumes that: -Proposed musical program can help to ensure belonging and maintaining the Egyptian identity of the kindergarten child. -There are statistically significant differences between the average scores of the children at international schools regarding belonging and maintaining Egyptian identity through using Egyptian musical songs during training of the post-test in favor of the experimental group. Methodology and Sample of the Research: This research uses the experimental approach "one group". The research sample consists of a group of children at the second stage of kindergarten within Sunrise International School in Heliopolis with (15) children. Research Tools: -Questionnaire form for the referees of the post and pre-test to measure the belonging level of the kindergarten child within international schools (prepared by the researcher) -Questionnaire form about the proposed musical songs for kindergarten child within international schools. -Interviews with a group of kindergarten children at Sunrise International School in Heliopolis about the type of songs and its role in developing homeland belonging. -Group of Egyptian musical songs that contains some concepts that develop belonging of the child at international schools. The research is divided into two parts: First: Theoretical Framework, that includes: 1-Previous Arabic and foreign studies related to the topic of research. 2-Belonging and identity that includes: definition of belonging - manifestations of belonging - alternatives to national belonging - belonging levels - definition of identity - some facts about the reality and dimensions of identity. 3-International schools that includes: the term of international schools - characteristics of international schools - the educational and cultural problem of the existence of a different educational system from the original environment - negative impacts of the spread of the culture of international schools. 4-Music and kindergarten child that includes: objectives of teaching music to the child - child song - educational objectives of child song. Second: Application (Practical) Framework, that includes: *Experiment procedures. *Sessions of the proposed program: 5 sessions. -Research results and its interpretation: By reviewing the research results, it become clear that the musical program proposed by the researcher increases the effectiveness of belonging of the kindergarten child at international schools. In the light of the response to the research hypotheses, the results of the first hypothesis showed the presence of statistically significant differences in favor of children scores in the post-test. It also achieve a high belonging level and maintaining the Egyptian identity of the kindergarten child at the international schools. This proves that the proposed musical program helped to ensure belonging and maintain the Egyptian identity of the kindergarten child. In addition, results of the second hypothesis showed the presence of statistically significant differences between the total scores of the pre-test and the post-test. The answers was in favor of the total scores of the post-test. The impact of the experiment reached 93.4% referring to the big success of the experiment in terms of the children total scores. According to the previous results, it becomes clear that the proposed musical program by the researcher increases the effectiveness of belonging of the kindergarten children at international schools. Research recommendations: -Researcher recommends the necessity of teaching the proposed program within the current study to develop the belonging of children at international schools. -The need to pay attention to the use of all musical activities provided to the kindergarten children at international schools to develop belonging and maintain the Egyptian identity. -Paying attention to teach the Egyptian songs at international schools to maintain the Egyptian identity of the kindergarten child. - References.
Keywords: الموسيقى -- الانتماء -- الهوية -- طفل الروضة